GRB 221009A: Revealing a Hidden Afterglow during the Prompt Emission Phase with Fermi-GBM Observations - Hai-Ming Zhang; Yi-Yun Huang; Ruo-Yu Liu; Xiang-Yu Wang (The Astrophysical Journal Letters, 2023)
Recently, LHAASO reported the detection of the brightest-of-all-time GRB 221009A, revealing the early onset of a TeV afterglow. We analyze the spectral evolution of the X-ray/gamma-ray emission of GRB 221009A measured by the Fermi Gamma-ray Burst Monitor (GBM) during the dips of two prompt emission pulses (i.e., intervals T _0 + [300–328] s and T _0 + [338–378] s, where T _0 is the GBM trigger time). We find that the spectra at the dips transit from the Band function to a power-law function, indicating a transition from the prompt emission to the afterglow. After ∼ T _0 + 660 s, the spectrum is well described by a power-law function, and the afterglow becomes dominant. Remarkably, the underlying afterglow emission at the dips smoothly connect with the afterglow after ∼ T _0 + 660 s. The entire afterglow emission measured by GBM can be fitted by a power-law function F ∼ t ^−0.95±0.05 , where t is the time since the first main pulse at T * = T _0 + 226 s, consistent with the TeV afterglow decay measured by LHAASO. The start time of this power-law decay indicates that the afterglow peak of GRB 221009A should be earlier than T _0 + 300 s. We also test the possible presence of a jet break in the early afterglow light curve, finding that both the jet break model and single power-law decay model are consistent with the GBM data. The two models cannot be distinguished with the GBM data alone because the inferred jet break time is quite close to the end of the GBM observations.